Determination of cheese suitability of milk and development of production technology of soft cheese 'Academicheskiy'. Issue 1 (November 2020) - Larionov, G; Semenov, V; Mardaryeva, N; Schiptsova, N; Lavrentyev, A; Checheneshkina, O; Terentyeva, M
Abstract: Cheese makers conduct research to improve the recipe and technology of cheese production. In Russia, the main raw material for cheese production is cow's milk. The aim of the research is to study the cheese suitability of milk and to improve the technology for production of soft cheese 'Academicheskiy'. The physical and chemical properties of milk were studiedby ultrasound method. The results of studies of milk quality were taken into account in developing the recipe and production technology of soft cheese. The cheese recipe included cow's milk, sour milk whey and salt. Soft cheese was made by hand using a thermal-acid method. The production technology of soft cheese 'Academicheskiy' consists of the following operations: acceptance of milk and additional raw materials; processing and preparation of milk; pasteurization of milk and sour whey at high temperature; mixing of milk and sour whey for protein precipitation; molding and self-pressing; salting; drying and maturation; packaging and labeling; storage, transportation and sale of soft cheese.